2009
DOI: 10.2217/pgs.09.80
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1 Haplotypes in Five East-Asian Populations and Indians

Abstract: Our data showed that 497T>G is only polymorphic in the Indian population. The 497G allele is very rare in the East-Asian populations (frequency < 1%). The remaining SNPs demonstrated high linkage disequilibrium and had similar frequencies and haplotype structures in all but the Indian population. The Indian population is mostly made up of the H7 haplotype (76%) while the rest of the recruited populations consisted of the H1 haplotype (> 80%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(23 reference statements)
1
15
1
Order By: Relevance
“…A recent study by Gan et al showed that among the Asian populations, Indians require higher warfarin doses compared with the Chinese and Malay patients, and these variations could mainly be due to different allele frequencies and polymorphisms in CYP2C9 and VKORC1 [9]. These results were further supported by findings of others who demonstrated that the VKORC1 haplotype in Indians was significantly different from other Asian populations [10,11]. It is thus imperative to ascertain differences in genotype frequencies in smaller populations within countries such as India to aid in the understanding and prediction of population level differences in drug metabolism and action.…”
Section: Introductionmentioning
confidence: 69%
“…A recent study by Gan et al showed that among the Asian populations, Indians require higher warfarin doses compared with the Chinese and Malay patients, and these variations could mainly be due to different allele frequencies and polymorphisms in CYP2C9 and VKORC1 [9]. These results were further supported by findings of others who demonstrated that the VKORC1 haplotype in Indians was significantly different from other Asian populations [10,11]. It is thus imperative to ascertain differences in genotype frequencies in smaller populations within countries such as India to aid in the understanding and prediction of population level differences in drug metabolism and action.…”
Section: Introductionmentioning
confidence: 69%
“…Consequently, the combined G/A and A/A genotype frequencies ranged from 19.7% (African–American) to 77.5% (Asian). However, the Asian g.-1639G>A frequency significantly deviated from Hardy–Weinberg equilibrium (p < 0.0001), presumably as a result of subpopulation heterogeneity [23,24], as our Asian cohort was comprised of different ethnicities.…”
Section: Resultsmentioning
confidence: 91%
“…This included 1306 subjects from the IWPC cohort (138 with genotype information only); 317 subjects from 6 different Asian countries with genotype information only 41 ; 316 subjects from 5 countries in South America, Africa, and the Middle East with genotype information only who were recruited as part of the PharmacoGenetics for Every Nation Initiative 42 ; and 6812 participants (2108 non-Hispanic blacks, 2631 nonHispanic whites, and 2073 Mexican Americans) ascertained as part of the Third National Health and Nutrition Examination Survey (NHANES), a population-based, racially representative cross-sectional study in the United States 43 (http://www.cdc.gov/nchs/nhanes.htm).…”
Section: Worldwide Haplotype Surveymentioning
confidence: 99%